eLingua : Issue 2 : June 2021 / Academy of Language Studies - Marimuthu, Rasaya; Mohd Adam, Aileen Farida; Zulkifli, Che Nooryohana; Mathai, Emily Jothee; Lim, Teck Heng; Versay Kudus, Nazima; Affendy Lee, Noor Azli; Mohd Amin, Noraziah; Adnan, Nur Ilianis; Ong, Sheau Fen; Ismail, Rushita; Seng, Hui Zanne; et al. (Academy of Language Studies, 2021)
1. International Workshop, Seminar, and Innovations (IWSI): Japanese Meet Malays - When Languages and Cultures Dance Together 2. 11th Malaysia International Conference on Languages, Literatures and Cultures (MICOLLAC2020) 3. A Meeting between Two Cultures 4. “PROJEK MINI PERPUSTAKAAN DAN PENYAMPAIAN ILMU, APB PRIHATIN ANAK BANGSA TERPIMPIN” BY ACADEMY OF LANGUAGE STUDIES, UiTM CAWANGAN PULAU PINANG 5. An Interview with Tuan Hj. Md Tahir bin Saad 6. ‘Getting to know you more’ Featuring ... Mr. Liaw Shun Chone 7. Program JLC (Japanese Language Club) UiTM Cawangan Pulau Pinang Sepanjang Tahun 2020 8. Third Language Corner 9. Closing Ceremony of ASiD Innovation and Creative Day 2021 (AICD 2021) 10. e-SULAM INNOVATE 2021 (IDEATION, INVENTION AND INNOVATION CHALLENGE) 11. Malay confinement: Myths and Current Practices 12. Head over meals - The evolution of nasi kandar 13. Head over meals - My Mum's Chocolate Chip Cookies recipe 14. lecturer's Contribution - Lead by Example 15. lecturer's Contribution - What if you do not know English? 16. lecturer's Contribution - A Brief Encounter with the World Games G.O.A.T 17. lecturer's Contribution - PELAJARAN MAMPU MENGUBAH MASA DEPAN ANGAH KYOIKU WA ANGAH NO MIRAI WO HENKOU SURU KOTO 18. The creative corner